2009
DOI: 10.1103/physrevd.80.064026
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic g-modes in rapidly rotating neutron stars

Abstract: We study the g-modes of fast rotating stratified neutron stars in the general relativistic Cowling approximation, where we neglect metric perturbations and where the background models take into account the buoyant force due to composition gradients. This is the first paper studying this problem in a general relativistic framework. In a recent paper [1], a similar study was performed within the Newtonian framework, where the authors presented results about the onset of CFS-unstable g-modes and the close connect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 40 publications
(71 reference statements)
2
54
0
Order By: Relevance
“…The asymptotic behavior of the homogeneous solution is given by setting α = 0 in Eq. (92), which is the same as Eq. (90) withω c being replaced by w c .…”
Section: Solution To O(χ )mentioning
confidence: 57%
See 2 more Smart Citations
“…The asymptotic behavior of the homogeneous solution is given by setting α = 0 in Eq. (92), which is the same as Eq. (90) withω c being replaced by w c .…”
Section: Solution To O(χ )mentioning
confidence: 57%
“…(80) and (84), while the asymptotic behavior of the solution that is regular at the NS center is given in Eq. (92). The asymptotic behavior of the homogeneous solution is given by setting α = 0 in Eq.…”
Section: Solution To O(χ )mentioning
confidence: 99%
See 1 more Smart Citation
“…Also another version of the iterated CN method was proposed in [5] and it was found that the last algorithm has better properties even providing only the first order of accuracy. Different versions of the iterated CN method were used in numerical relativity by a number of authors (e.g., [3,4,[6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Only the non-axisymmetric modes, though, are prone to CFS instability. Because of the complexity of the problem, most of the studies in this case were performed in the linear regime employing the Cowling approximation [3,4,27,29,30,32], where the spacetime degrees of freedom are neglected and only the fluid variables are evolved in time. The only exceptions are the studies in the conformal flatness approximation [26,31] where a few exemplary sequences with polytropic equation of state where examined, and the full general relativistic nonlinear results in [28].…”
Section: Introductionmentioning
confidence: 99%